TOOTH IMPRINTS AND QUANDARY (Journal of Forensic Medicine & Toxicology, 2025)
The primary aim of this review is to initially analyze the research conducted in India and around the world, focusing on diverse aspects related to bite marks such as their presentation in various media, causative factors, potential distortions, and various techniques to interpret them. Secondly, it aims to scrutinize and summarize resolved cases around the globe that have been documented over the past years, including cases reported in India. Systematic search for articles was done using search engines, including “PubMed, Medline, Embase, Google Scholar, Scopus, and Web of Science”. Bitemarks may be an intriguing tool to be employed in criminal investigations and may be able to provide insight into a case. Forensic Odontologists have been accused of misrepresenting the unique nature of human dentition and of disregarding the unpredictable nature of tooth marks on the skin. As a result, bitemark evidence has been characterized as unreliable due to its lack of sensitivity and specificity, leading critics to assert that any conclusions drawn from bitemark evidence must be invalid. Throughout this review, we have analyzed various studies conducted worldwide and tabulated them according to different criteria. Furthermore, solved cases have been reviewed to see the effectiveness of BM cases solved and presented in court of Law.
Keywords: Bite Marks; computer generated overlays; hand docking; forensic odontology; ASFO